Ideology Versus Clientelism: Modernization and Electoral Competition in Brazil - (:unkn) unknown (My University, 2015)
This study investigates how parties utilize the political dimensions of ideology (left-right) and clientelism (programmatic-patronage) to compete electorally in developing democracies. It proposes a combined utility theory, which suggests polarized competitive elections in modernizing national electoral markets compel programmatic parties to coalesce with clientelistic parties to gain access to regional private electoral markets. Methodologically, this study draws on a mixed-method approach focusing on Brazil as a crucial test case. It applies spatial voting models to assess the validity of ideological competition as well as geospatial voting distribution based on clustering and dispersion to devise a new quantitative measurement of clientelism based on subnational electoral market characteristics. Field research helps uncover how political elites form strategically combined ideological and clientelistic party coalitions to increase electoral success. The analysis suggests ideology and clientelism operate as independent factors explaining political linkages in developing democracies. The interaction of these dimensions through electoral coalitions, however, indicates the weakening of ideology over time and lack of discernible pattern on the clientelistic level. This study contributes to the literature by investigating party competition on the ideological and clientelistic levels. It also contributes to the analytical and methodological refinement of the concept of clientelism as a systematic political linkage.
Keywords: Brazil; Clientelism; Elections; Ideology; Modernization; Political Parties